Is It Reasonable to Perform Isolated SAVR by Residents in the TAVI Era? - Gerfer, Stephen; Eghbalzadeh, Kaveh; Brinkschröder, Sarah; Djordjevic, Ilija; Rustenbach, Christian; Rahmanian, Parwis; Mader, Navid; Kuhn, Elmar; Wahlers, Thorsten (The Thoracic and Cardiovascular Surgeon, 2021)
Background The role of conventional surgical aortic valve replacement (SAVR) is increasingly questioned since the indication for transcatheter aortic valve implantations (TAVIs) is currently extended. While the number of patients referred to SAVR decreases, it is unclear if SAVR should be performed by junior resident surgeons in the course of a heart surgeons training.Methods Patients with isolated aortic valve replacement (AVR) were analyzed with respect to the surgeon's qualification. AVR performed by resident surgeons was compared with AVR by senior surgeons. The collective was analyzed with respect to clinical short-term outcomes comparing full sternotomy (FS) with minimally invasive surgery and ministernotomy (MS) with right anterior thoracotomy (RAT) after a 1:1 propensity score matching.Results The 30-day all-cause mortality was 2.3 and 3.4% for resident versus senior AVR groups, cerebrovascular event rates were 1.1 versus 2.6%, and no cases of significant paravalvular leak were detected. Clinical short-term outcomes between FS and minimally invasive access, as well after MS and RAT were comparable.Conclusion Our current data show feasibility and safety of conventional SAVR procedure performed by resident surgeons in the era of TAVI. Minimally invasive surgery should be trained and performed in higher volumes early in the educational process as it is a safe treatment option.
Keywords: aortic stenosis; surgical aortic valve replacement; full sternotomy; minimal invasive; upper-J ministernotomy; right anterior thoracotomy; resident; senior; surgical technique